2020
DOI: 10.1186/s12889-020-09777-0
|View full text |Cite
|
Sign up to set email alerts
|

Early sexual initiation and risky sexual practices among alcohol- and tobacco-using young adults in Taiwan: mediation analysis of preceding-sex use of illicit drugs

Abstract: Background As early sexual initiation is increasingly common in East Asia, we examined its relations to risky sexual practices in alcohol- and tobacco-using individuals in Taiwan and evaluated whether the associations were mediated through preceding-sex use of illicit drugs. Methods Participants, recruited from alcohol- and tobacco-using adults aged 18 to 50 in Taipei through respondent-driven sampling (N = 1115), completed a compute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 58 publications
0
7
0
2
Order By: Relevance
“…Based on this, the overall prevalence of early sexual initiation among youth females in -sub-Saharan Africa was 46.39% [95%CI: 41.23%, 51.55%).] which is higher than a study conducted in Indonesia 11% [ 25 ], brazil, 7% [ 10 ], Taiwan 9.3% [ 26 ] and china 18.1% [ 9 ]. The variations might be related to factors associated with early sexual initiation of these countries being high-income countries with improved socio-economic status, youth females education, gender equity, and reproductive health youth female are services compared to SSA, which in turn could improve their levels of understanding of the consequences of early sexual initiation [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 61%
“…Based on this, the overall prevalence of early sexual initiation among youth females in -sub-Saharan Africa was 46.39% [95%CI: 41.23%, 51.55%).] which is higher than a study conducted in Indonesia 11% [ 25 ], brazil, 7% [ 10 ], Taiwan 9.3% [ 26 ] and china 18.1% [ 9 ]. The variations might be related to factors associated with early sexual initiation of these countries being high-income countries with improved socio-economic status, youth females education, gender equity, and reproductive health youth female are services compared to SSA, which in turn could improve their levels of understanding of the consequences of early sexual initiation [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 61%
“…There is also an emphasis on the individual expectation of alcohol opening the door to positive sexual experiences, with greater excitement and sexual disinhibition 32,33 . The abusive use of illicit substances, by contrast, frequently lead the user to a strong desire of the drug, favoring the nonuse of a condom and the practice of violent acts to acquire it 21,34 . The association of substances amplifies these outcomes; however, the isolated effect of illicit drugs is greater than that of alcohol and cigarettes regarding RSB 34 .…”
Section: Discussionmentioning
confidence: 99%
“…The EOSI has been associated with having multiple sexual partners, paying for sex, inconsistent use of contraception ( 44 ), group and/or casual sex ( 12 ), and depression ( 30 ). These also represent risk factors of STI transmission, thus supporting its association with the EOSI.…”
Section: Discussionmentioning
confidence: 99%
“…Our study also demonstrated an association between the EOSI and STIs in women with <2 sexual partners during the last year, which might be accounted for by the inconsistent use of condoms, leading to a higher risk of STI transmission ( 55 ). Furthermore, it is important to highlight that several STIs are chronic and could be previously contracted by the women with an EOSI through transmission by the multiple sexual partners they might have had throughout their lives or prior to the year of evaluation ( 56 ), or due to their history of other sexually risky behaviors, such as casual or group sex ( 12 ). In addition, a cause of the EOSI in women is sexual abuse at an early age ( 57 ), wherein the sexual activities usually occurred without the use of condoms ( 58 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation